Single-step laser sintering of YSZ powder-beds to TBC applications - V. T. Mazur; D. C. Chagas; M. M. Mazur; S. A. Pianaro; G. de Vasconcelos (Cerâmica, 2021)
Abstract Ceramics are widely employed as thermal insulating materials for thermal barrier coatings (TBC) due to their low thermal conductivity, chemical stability, and high wear and corrosion resistance at high temperatures. The aim of this work was to study the influence of the CO2 laser beam parameters on the single-step irradiation of pre-placed yttria-stabilized zirconia (YSZ) powders on NiCrAlY/AISI 316L substrates. In order to increase the coating’s lifetime and performance, it is proposed a laser sintering of powder-beds (LSP) technique to obtain homogenous YSZ coatings, with controlled surface microstructures. The obtained coatings were characterized by optical microscopy, field emission scanning electron microscopy, energy dispersive spectroscopy, and X-ray diffraction (XRD). The laser intensity and interaction time were the main laser parameters used to control the surface temperature and the combination of these parameters were used to establish a process chart. The LSP resulted in controlled smooth coating surfaces and columnar growth with submicrometric grain size. XRD analyses showed the prevalence of non-transformable tetragonal zirconia, which is known to exhibit higher stability and thermal wear resistance.